2015
DOI: 10.1021/acsami.5b08385
|View full text |Cite
|
Sign up to set email alerts
|

Ru Catalyst-Induced Perpendicular Magnetic Anisotropy in MgO/CoFeB/Ta/MgO Multilayered Films

Abstract: The high oxygen storage/release capability of the catalyst Ru is used to manipulate the interfacial electronic structure in spintronic materials to obtain perpendicular magnetic anisotropy (PMA). Insertion of an ultrathin Ru layer between the CoFeB and Ta layers in MgO/CoFeB/Ta/MgO films effectively induces PMA without annealing. Ru plays a catalytic role in Fe-O-Ta bonding and isolation at the metal-oxide interface to achieve moderate interface oxidation. In contrast, PMA cannot be obtained in the sample with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 33 publications
1
10
0
Order By: Relevance
“…Specifically, for the regions in contact with Pt, μ 0 M eff false( Pt false) = 95.8 mT, and for the case of Ru, μ 0 M eff false( Ru false) = 75.8 mT, for an exchange constant A ex = 15.62 pJ/m and an i-DMI strength D = 1.1 mJ/m 2 in the Pt zones. In particular, the lower value of M eff in the region in contact with Ru can be ascribed not only to the perpendicular magnetic anisotropy but also to a reduction of the saturation magnetization due to the interdiffusion and dead layer formation at the Ru/CoFeB interface. The positive value of M eff indicates a remanent state with in-plane magnetization, as found experimentally.…”
mentioning
confidence: 63%
“…Specifically, for the regions in contact with Pt, μ 0 M eff false( Pt false) = 95.8 mT, and for the case of Ru, μ 0 M eff false( Ru false) = 75.8 mT, for an exchange constant A ex = 15.62 pJ/m and an i-DMI strength D = 1.1 mJ/m 2 in the Pt zones. In particular, the lower value of M eff in the region in contact with Ru can be ascribed not only to the perpendicular magnetic anisotropy but also to a reduction of the saturation magnetization due to the interdiffusion and dead layer formation at the Ru/CoFeB interface. The positive value of M eff indicates a remanent state with in-plane magnetization, as found experimentally.…”
mentioning
confidence: 63%
“…The efforts to engineer novel interface structures are often hindered by difficulties reconciling the properties of ultrathin films at macroscopic and microscopic scales. The CoFeB/MgO interface forms the basis of magnetic tunnel junction (MTJ) technology due to its tunneling magnetoresistance (TMR) and perpendicular magnetic anisotropy (PMA). Subjecting the thin MgO tunnel barrier in MTJs to repeated electrical stress induces breakdown, which limits the endurance of magnetoresistive random-access memory (MRAM) devices. This situation is similar to the time-dependent dielectric breakdown (TDDB) in complementary metal-oxide–semiconductor (CMOS) gate oxides. Researchers have reported that the breakdown can be delayed by inserting an ultrathin film of metallic Mg into the CoFeB/MgO interface during MgO barrier formation to prevent CoFeB oxidization. Mg termination has also been shown to suppress the magnetic dead layer in ferromagnetic electrodes. …”
Section: Introductionmentioning
confidence: 99%
“…The key to achieve a perpendicular-anisotropy CoFeB/MgO MTJ is the very thin thickness of CoFeB layer. 23,24 The PMA was attributed entirely to the CoFeB-MgO interfacial anisotropy by Ikeda et al, 8 while the Ta seed layer, not just the MgO at the top interface, was demonstrated to be critical to achieving perpendicular magnetic anisotropy. 25 The microscopic origin of the PMA in the CoFeB/MgO structure is still far from clear.…”
Section: Introductionmentioning
confidence: 99%